2009
DOI: 10.1021/jf803680c
|View full text |Cite
|
Sign up to set email alerts
|

Universal DNA-Based Methods for Assessing the Diet of Grazing Livestock and Wildlife from Feces

Abstract: Because of the demand for controlling livestock diets, two methods that characterize the DNA of plants present in feces were developed. After DNA extraction from fecal samples, a short fragment of the chloroplastic trnL intron was amplified by PCR using a universal primer pair for plants. The first method generates a signature that is the electrophoretic migration pattern of the PCR product. The second method consists of sequencing several hundred DNA fragments from the PCR product through pyrosequencing. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 40 publications
0
80
0
Order By: Relevance
“…For example, biased amplification can occur when the primers match better sequences in certain species over others (Shehzad et al, 2012b), or because of preferential amplification of shorter sequences (Rayé et al, 2011). Biological factors, such as variation in the proportion of mitochondrial and chloroplast organelles among tissues and differential digestibility of foods, may also influence DNA quantity in the scats and therefore its detectability for diet analysis (Pegard et al, 2009;Deagle et al, 2010;Thomas et al, 2014). Even if these constraints preclude the use of sequence read counts for accurate absolute quantitative interpretations of the proportions of food ingested, various studies showed that consistent proportions of food DNA were estimated from fecal samples of animals fed a known diet (Deagle et al, 2010;Bowles et al, 2011), and that DNA sequence counts can be used for semiquantitative estimates of diet in comparative studies (Pompanon et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, biased amplification can occur when the primers match better sequences in certain species over others (Shehzad et al, 2012b), or because of preferential amplification of shorter sequences (Rayé et al, 2011). Biological factors, such as variation in the proportion of mitochondrial and chloroplast organelles among tissues and differential digestibility of foods, may also influence DNA quantity in the scats and therefore its detectability for diet analysis (Pegard et al, 2009;Deagle et al, 2010;Thomas et al, 2014). Even if these constraints preclude the use of sequence read counts for accurate absolute quantitative interpretations of the proportions of food ingested, various studies showed that consistent proportions of food DNA were estimated from fecal samples of animals fed a known diet (Deagle et al, 2010;Bowles et al, 2011), and that DNA sequence counts can be used for semiquantitative estimates of diet in comparative studies (Pompanon et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A sequence reference database was built for each molecular marker analyzed, applying the programs ecoPCR (Ficetola et al, 2010) and OBITools, using the sequences of the plant database generated for this study and recovering the relevant part of the molecular markers from the EMBL database (release 117). These reference databases were used to assign the taxon to the diet sequences using ecotag program (Pegard et al, 2009).…”
Section: Filtering and Annotating Sequences Of The Diet Data Setmentioning
confidence: 99%
“…However, this method does yet allow quantification, because it does not take into account variation in rate of digestion of different plant species or plant parts (Fraser et al, 2006). Recently, some methods have been developed based on plant DNA identification in faeces to characterize diet composition at species level, with encouraging results (Valentini et al, 2008;Pegard et al, 2009), but are not enough advanced to enable per-species intake quantification. The analysis of n-alkanes, long-chain fatty alcohols and long-chain fatty acids in faeces as diet composition markers has recently been improved to quantify intake at species level (Ali et al 2005) and applied to animals either consuming controlled simple diets (Kelman et al, 2003;Ali et al, 2004Ali et al, , 2005Ferreira et al 2009) or grazing moderately-diversified swards (Fraser et al, 2006(Fraser et al, , 2009, with encouraging results.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the data is exposed to the influence of observer error (Fraser et al, 2006). Several other methods have been developed to quantify the composition of diet consumed by animal grazing heterogeneous grasslands: analysis of extrusa collected from esophageally fistulated animals (Fraser and Gordon, 1997), DNA or micro-histological analyses on faeces (Valentini et al, 2008;Pegard et al, 2009), faecal analysis of longchain fatty alcohols, long-chain fatty acids and n-alkanes (Kelman et al, 2003;Ali et al, 2004Ali et al, , 2005Ferreira et al 2009). These methods are however characterized by high analytical costs and complex application, or are not yet developed enough to quantify species intake in nonexperimental grazing conditions on highly biodiverse pastures.…”
Section: Introductionmentioning
confidence: 99%
“…Dung counts are not influenced to the same degree by the difficulties associated with seasonal and diurnal variation in animal visual detection and the technique may also provide information on habitat use, and population distribution and size (Bennett et al 1940;Putman 1984;Chapman et al 1985;Lamoot et al 2004;Acevedo et al 2008;Mathur et al 2011). In some herbivore species, faecal shape and size can be used to identify the population sex and age structure, while in other species faecal chemistry permits assessment of animal dietary quality (Bubenik 1982;Sinclair et al 1982;Coe and Carr 1983;Maccracken and van Ballenberghe 1987;Pegard et al 2009). …”
Section: Photo: Magdalena Zabekmentioning
confidence: 99%